FACTORS INFLUENCING DEVELOPING AGRICULTURE MARKET WITH RESPECT TO FARMER PRODUCING COMPANIES IN PUNE DISTRICT - Pawar , Anil Nivrutti; Gosavi , Yogesh Mohan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the factors influencing the development of agricultural markets and the challenges faced by farmer-producing companies (FPCs) in effectively marketing their produce. Data was collected through a structured questionnaire administered to 100 FPC directors, focusing on the role of infrastructure, financial access, technology adoption, and government support in market growth, as well as the challenges related to market access, transportation infrastructure, price fluctuations, product quality consistency, and bargaining power. The study employs a One-Sample t-test to analyze the data and test the hypotheses. The findings indicate that modern infrastructure, access to financial support, technological adoption, and government policies are crucial for the success of FPCs in expanding agricultural markets. However, challenges such as limited market information, inadequate transportation, fluctuating prices, inconsistent product quality, and insufficient bargaining power were identified as significant barriers. These results highlight the need for targeted interventions to support FPCs in overcoming these challenges and enhancing their market reach. The study’s implications provide valuable insights for policymakers, FPC leaders, and stakeholders in fostering the development of agricultural markets in emerging economies.